Organizational assessment : a framework for improving performance - Lusthaus, Charles (International Development Research Centre, 2002)
This book offers a clear-cut methodology to diagnose institutional strengths and weakness at the onset of development activities. The authors examine all aspects of organizational performance, including the enabling environment, institutional capacity, management, financial viability, and staff motivation.